Combating Cognitive Dysfunction among CKD Patients: Need for Effective Treatment Module - Shikha, U. V. Kiran, (Journal for ReAttach Therapy and Developmental Diversities, 2023)
CKD (Chronic kidney disease) is a non-communicable usually caused and manifested by diabetes and hypertension. It worsens over time and leads to both physical and psychological health problems. Over 10% of people globally have CKD, a critical and rapidly progressing illness. Depression, cognitive dysfunction, and a poor quality of life are all associated with deteriorated renal function. Chronic kidney disease (CKD), a causative agent for morbidity and mortality, becoming a more serious health concern globally. According to recent research, there is a 20 to 50% prevalence of cognitive dysfunction in the CKD population, with a 70% increase among the older population of patients undergoing maintenance Hemodialysis. There is a high incidence of cognitive disorders and impairment in the CKD population, with anxiety, depression, and stress being reported by 63.9%, 60.5%, and 51.7% of patients with CKD, respectively. In individuals with chronic renal failure, cognitive function is impeded by a lack of mental and physical exercise. The multiple benefits of frequent, appropriate physical activity for health are well supported by research. Hemodialysis patients are reported to be more likely to experience cognitive abnormalities in numerous studies. Studies have shown a strong link between increased physical activity and a lower risk of cognitive decline and dementia. People with reduced kidney function can benefit from exercising regularly just like those without this condition. Therefore, the challenge is to develop an integrated treatment model for physical activity and exercise that is safe, feasible, and sustainable for chronic kidney disease patients and also educate patients on adherence. The goal of the study is to highlight the critical role of intervention module and its implementation as effective preventive and treatment measure for patients in all stages of CKD. This review is to educate patients, their caregivers, and kidney care specialists about the importance of physical activity and exercise in all phases of CKD as well as the implementation of recommendations that have been clinically proven to be effective in both preventing and treating cognitive dysfunction not only in healthy people but also in patients suffering from kidney disease or deteriorated kidney function.